A nationwide 104 weeks real‐world study of dupilumab in adults with atopic dermatitis: Ineffectiveness in head‐and‐neck dermatitis. (21st January 2023) - Vittrup, Ida; Krogh, Niels Steen; Larsen, Henrik Hedegaard Pliess; Elberling, Jesper; Skov, Lone; Ibler, Kristina Sophie; Jemec, Gregor B. E.; Mortz, Charlotte G.; Bach, Rasmus Overgaard; Bindslev‐Jensen, Carsten; Dalager, Maiken Glud; Egeberg, Alexander; et al.
Abstract: Background: Evaluation of effectiveness and safety of new systemic treatments for atopic dermatitis (AD) after approval is important. There are few published data exceeding 52‐week therapy with dupilumab. Objectives: To examine the safety, effectiveness and drug survival of dupilumab in a Danish nationwide cohort with moderate‐to‐severe AD up to 104 weeks exposure. Methods: We included 347 adult patients with AD who were treated with dupilumab and registered in the SCRATCH registry during 2017–2022. Results: At all visits, we observed improvement in AD severity measured by Eczema Area and Severity Index (EASI) [median (IQR)]. EASI score at baseline was 18.0 (10.6–25.2), at week 4: 6.5 (3.5–11.6), at week 16: 3.7 (1.2–6.2), at week 52: 2.0 (0.8–3.6), at week 104: 1.7 (0.8–3.8). While drug survival was high (week 52: 90%; week 104: 86%), AD in the head‐and‐neck area remained present in most patients at high levels; proportion with head‐and‐neck AD at baseline was 76% and 68% at week 104. 35% of patients reported any AE. Conjunctivitis was the most frequent (25% of all patients) and median time to first registration of conjunctivitis was 201 days. Conclusions: While 2‐year drug survival was 86%, dupilumab was unable to effectively treat AD in the head‐and‐neck area, and conjunctivitis was found in 25% of patients.